Processos Antropogênicos Induzidos em meios urbanizados, seu estudo a partir da Geomorfologia Antropogênica no município de Uberlândia - MG - Danelon, Jean Roger Bombonatto (2023)
Anthropogenic Geomorphology is an offshoot of geomorphological science responsible for studying the alterations carried out on the landform surface caused by human activities. Considering human actions as forces that modify and alter the Earth landform is something of fundamental importance, because anthropic activities have gained increasingly proportion and relevance on the Earth surface. The urban clusters undoubtedly represent the greatest symbol of anthropic action on the planet, given that since the beginning of modern civilizations cities have been multiplying across territories and occupying ever larger areas. There are currently a large number of metropolises on the planet that are the backdrop for the daily activities of their populations. However, it is necessary to pay attention that for these urban clusters to take on such proportions, many actions were necessary, among which, the modification of the landform surface in order to make the implantation of urban sites feasible stands out with notoriety. Natural landscapes tend to have a dynamic balance between energy and material flows, since each natural action self-regulates within a period of time. However, from the implementation and evolution of the urban site, this balance is broken and other forces start to act and modify the flows of energy and matter, among these we focus on the geomorphological processes occurring in urbanized environments, trying to analyze their genesis and dynamics of operating in these locations. For this, it was necessary to make a conceptual distinction of these geomorphological processes, as they have particularities that distinguish them from the geomorphological processes occurring in non-urbanized environments. In this context, the concept of anthropogenic induced processes (A.I.P) was proposed, aiming to define the geomorphological and hydrogeomorphological processes, which are likely to be directly related to anthropic actions, which have been the initial or preponderant mechanism for their occurrence or aggravation. Their identification followed the following steps: identification of existing geomorphological processes; analysis of the dynamics of these processes; point out the existence of conditioning factors (influencers and structural controllers); and analyze whether there is a relationship between the identified processes and the existence of influencing and controlling factors that can be characterized as P.A.I. Among the anthropogenic induced processes presented are: ravines and gullies of anthropogenic origin; anthropogenic piping processes; high diffusion runoff; and anthropogenic floods. After the exposition and discussion carried out regarding the anthropogenic induced processes, it was possible to infer that using such an anthropogenic character approach is presented as a relevant tool in the study and understanding of urbanized landscapes, since these landscapes are dynamic and complex, demanding skills that are representative for its effective analysis and understanding.